Analisis Efisiensi dengan Menggunakan Metode Data Envelopment Analysis pada Bank Umum Syariah - Syifa Ikrima Fauziah; Erry Sunarya; Kokom Komariah (Journal of Management and Bussines (JOMB), 2019)
The purpose of this study is to determine the level of efficiency in Islamic banks using the data envelopment analysis method. This type of research is quantitative research. The research method used in this study is to use data envelopment analyis (DEA). Data analysis techniques using DEAP version 2.1 software. The results of the study, Islamic banks are said to be efficient if they reach level 1 or 100%. The inputs used are assets, total deposits, operating costs and output are operating income and financing. This study uses 5 Sharia Commercial Banks namely Bank Muamalat Indonesia, Bank BNI Syariah, BCA Syariah Bank, Bank Syariah Mandiri and BRI Syariah Bank during the 2014-2016 period, there are only two banks that experience efficiency each year, namely Bank Muamalat Indonesia and Bank Syariah Mandiri. Conclusion, of the five Islamic banks there are only two banks that experience efficiency each year, namely Bank Muamalat Indonesia and Bank Syariah Mandiri. Keywords: Efficiency, Islamic Bank, Data Envelopment Analysis